The declines in infant mortality and fertility: Evidence from British cities in demographic transition - Andrew T. Newell; Ian Gazeley (Institute for the Study of Labor (IZA), 2012)
At the beginning of the twentieth century Britain was roughly halfway through a 60-year demographic transition with declining infant mortality and birth rates. Cities exhibited great and strongly correlated diversity in these rates. We demonstrate cross-section correlations with, for instance, women's employment, population density, literacy and improved water supply and sanitation, that have been linked to the transition. When we analyse data from the late 1850s and the early 1900s, the changes in the two rates are not correlated across cities, but we find a robust and large impact from sanitation improvement to long-period infant mortality reduction. We also find the extension of basic literacy is related to increases in female labour market participation, which is in turn related to fertility reduction. Lastly we find that more rapid urban growth accelerates fertility decline, but, in late 19th century Britain it slowed the reduction of infant mortality.
Keywords: N33; J13; I15; 330; fertility; infant mortality; education and sanitary reform; women's participation; education; 19th century and early 20th century Britain; Kindersterblichkeit; Fruchtbarkeit; Demographischer Übergang; Städtische Bevölkerungsentwicklung; Großbritannien